Cán bộ thư viện đại học trong quản lý hệ thống thông tin số hỗ trợ hành vi thông tin của người dùng tin - Bùi, Hà Phương (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The paper introduces the research on the information users' behavior towards academic libraries in the digital environment. Analyzing the role of librarians in managing digital information system to support users' information behavior.